2013
DOI: 10.1073/pnas.1316851110
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of gene flow and hybrid fitness between the M and S forms of the malaria mosquito, Anopheles gambiae

Abstract: The M and S forms of Anopheles gambiae have been the focus of intense study by malaria researchers and evolutionary biologists interested in ecological speciation. Divergence occurs at three discrete islands in genomes that are otherwise nearly identical. An "islands of speciation" model proposes that diverged regions contain genes that are maintained by selection in the face of gene flow. An alternative "incidental island" model maintains that gene flow between M and S is effectively zero and that divergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
171
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(180 citation statements)
references
References 68 publications
6
171
1
Order By: Relevance
“…In Selenkenyi, only 2 out of 280 backcrossed individuals were homozygous-susceptible (+/+), a significant deficiency relative to expected (N exp = 24.4; P < 0.0001 using randomization goodness of fit with 10,000 replicates). Lee et al (5) showed that an earlier hybridization episode in 2002, before the introduction of ITNs in Selenkenyi, was followed by strong selection against hybrids, presumably related to ecological maladaptation or decreased mating success. Thus, it appears that the introduction of L1014F in the presence of insecticide pressure was a key factor that allowed hybrids to overcome an intrinsic selective disadvantage and backcross with the A. coluzzii parental population, contributing to gene flow between the two species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Selenkenyi, only 2 out of 280 backcrossed individuals were homozygous-susceptible (+/+), a significant deficiency relative to expected (N exp = 24.4; P < 0.0001 using randomization goodness of fit with 10,000 replicates). Lee et al (5) showed that an earlier hybridization episode in 2002, before the introduction of ITNs in Selenkenyi, was followed by strong selection against hybrids, presumably related to ecological maladaptation or decreased mating success. Thus, it appears that the introduction of L1014F in the presence of insecticide pressure was a key factor that allowed hybrids to overcome an intrinsic selective disadvantage and backcross with the A. coluzzii parental population, contributing to gene flow between the two species.…”
Section: Resultsmentioning
confidence: 99%
“…Initially described as the M and S molecular forms, they are now recognized species, designated Anopheles coluzzii and Anopheles gambiae, respectively (1). The two species exhibit varying degrees of reproductive isolation (RI) across their range (2)(3)(4)(5)(6), and recent studies provide strong evidence for reduced hybrid fitness in nature (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Senegal study site at Dielmo and nine of our study sites were proximal (<50km) to the Atlantic Ocean, while Mali is a land-locked country at least 500km away from the Atlantic Ocean. Therefore, the discrepancy among studies may be due to climatic and environmental pressure on the different genetic backgrounds of A. gambiae observed in this area of West Africa ( Lee et al , 2013). More robust sampling over a larger number of collection sites would help in confirming this trend.…”
Section: Resultsmentioning
confidence: 99%